Marketing Communication Factors Affecting Consumers’ Decision to Use the Service of Slow Bar Type Coffee Shop that Uses a Moka Pot Brewing Method: A Case Study of Sweet Shine Coffee - Praphasongsit, Aeksirion; Bilmanoch, Sasiphan; Sanjit, korakot (Siam Communication Review, 2022)
The objectives of this research were (1) to study consumers' opinions on marketing communication factors of Sweet Shine Coffee shop; (2) to study consumers' opinions on their decision to use the service at Sweet Shine Coffee shop; (3) to compare. Consumer opinions towards the decision to use the Sweet Shine Coffee service classified by demographic characteristics (4) to study the relationship between marketing communication factors and the decision to use the Sweet Shine coffee service. It is a quantitative and qualitative research. Therefore, two sample groups were defined as follows: quantitative research. The researchers calculated the population who regularly used the Sweet shine coffee shop, which were approximately 1,200 people per month. From the list of receipts for the month of July 2021 of the service users using the formula to determine the size of the finished sample of Krejcie & Morgan. The confidence level was 95% and the error was 5%. A total of 400 researchers were randomly assigned to a specific group and the sample was determined in the qualitative research. The researcher used a method to select a specific sample (Purposive Sampling) from 10 people who came to use the service at the Sweet shine coffee shop. The instrument used in this research was a questionnaire. Marketing communication factors affecting the decision to use the slow bar coffee shop using the Moka Pot method of Sweet Shine coffee shop consisted of 3 parts and an interview form. Marketing and decision to use the service of Sweet shine coffee shop From 10 people who came to use the service at Sweet shine coffee shop, the instrument used in this research was a questionnaire on Marketing communication factors affecting the decision to use the slow bar coffee shop using the Moka Pot method of Sweet Shine coffee shop consisted of 3 parts and an interview form. Marketing and decision to use the service of Sweet shine coffee shop From 10 people who came to use the service at Sweet shine coffee shop, the instrument used in this research was a questionnaire on Marketing communication factors affecting the decision to use the slow bar coffee shop using the Moka Pot method of Sweet Shine coffee shop consisted of 3 parts and an interview form. Marketing and decision to use the service of Sweet shine coffee shop The results of the study revealed that the people who used the service at Sweet Shine Coffee, the respondents had different demographic relationships, the decision to use the Sweet shine coffee shop was different in all respects. There was a level of opinion about the marketing communication 7Ps of consumers who use the service at Sweet Shine Coffee shop overall at a high level with the highest average, followed by personnel or personnel, and physical characteristics and opinions about the decision to use the service at Sweet Shine Coffee of those who use the service the highest alternative assessment, followed by the purchase decision. and the perception of needs